Study of kinetics of medicinal substances release from chitosan films - Shurshina, Angela; Kulish, Elena; Lazdin, Roman (Publishing House of Lviv Polytechnic National University, 2015)
The kinetics of controlled release of medicinal substances from chitosan films has been investigated. Correlation between values of diffusion coefficients and the sedate indicator characterizing diffusion of medicinal substance from a film and shares of medicinal substance connected with a polymeric chain has been established. With the increase in amount of the entered medicinal substance the rate of release of medicines decreases. Досліджено кінетику контрольованого вивільнення лікарських речовин з хітозанових плівок. Встановлено взаємозв‘язок між значеннями коефіцієнту дифузії, показником, що характеризує режим дифузії, та часткою лікарської речовини, зв‘язаної з полімерною матрицею. Показано, що зі збільшенням кількості лікарської речовини швидкість їх вивільнення зменшується.
Вивчення кінетики вивільнення лікарських речовин з хітозанових плівок
Keywords: chitosan; medicinal substance; diffusion; the abnormal character; хітозан; лікарська речовина; дифузія; аномальний характер